Ambient air pollution and cardiorespiratory outcomes amongst adult residing in four informal settlements in the Western Province of South Africa - Bagula, Herman Joseph (Department of Public Health and Family Medicine, 2020)
Background Many studies investigating the relationship between ambient air pollution and cardiorespiratory outcomes have been conducted in developed countries despite more vulnerable populations in low- and middle-income countries especially in Africa. No studies previous studies have been done in South Africa informal settlements. Aim The aim of the study was to investigate the relationship between ambient air pollutant exposure and self-reported cardiorespiratory outcomes amongst adults residing in four informal settlements of the Western Province of South Africa. Methods This cross-sectional study included 572 adults from four informal settlements (Khayelitsha, Marconi Beam, Oudtshoorn and Masiphumele) in the Western Cape, South Africa. The study made use of Land Use Regression to estimate each participant’s exposure to particulate matter of aerodynamic diameter of 2.5µm (PM2.5) and nitrogen dioxide (NO2). A questionnaire was adapted from the European Community Respiratory Health Survey and National Health and Nutrition Examination Survey questionnaire to collect data on self-reported cardiorespiratory outcomes and specific confounding factors of interest. Results The median age the participants was 39 years (Interquartile Range (IQR): 33 - 45) with 88.5% female. The median NO2 level was 22.4 µg/m3 (IQR: 13.3 - 24.1) and the median PM2.5 level was 10.6 µg/m3 (IQR: 8.7 - 13.1). An increase of 10µg/m3 in annual NO2 level was found to be associated with a 2.9 (95%CI: 1.3 to 6.1) odds of having self-reported chest pain, adjusting for PM2.5 and confounders. No other significant association was found indicating an adverse health effect due to air pollution. Conclusion The study found preliminary circumstantial evidence of an association between annual ambient NO2 exposure and self-reported chest pain (a crude proxy of angina related pain), even at levels below both WHO Air Quality Guidelines and the South African National Ambient Air Quality Standards. However, the results should be interpreted cautiously due to the self-reported nature of the outcome measure and the cross-sectional design of the study.